A risk governance approach to managing antitrust risks in the banking industry - Denise Scheld; Johannes Paha; Nicolas Fandrey (Philipps-University Marburg, School of Business and Economics, 2015)
Competition law compliance has become increasingly important in the banking industry as the number of infringements and the associated fines imposed by the European Commission are rising. This article shows that not only governments and regulators, but also shareholders and managers, should be interested in managing antitrust risks in banks in order to avoid competition law infringements. Therefore, this article sets out an approach to assessing the residual risk of antitrust non-compliance as well as the costs associated with such conduct, in order to be able to identify the required intensity of risk management activities. It also shows how antitrust risk management can be implemented in banks' governance structures using the Three Lines of Defence model and the COSO ERM framework. As a result, it demonstrates how to integrate antitrust risk management activities into existing structures and processes, thus improving the efficiency and effectiveness of overall risk management, in particular antitrust risk management.
Keywords: G20; G30; G32; L21; K21; 330; risk management; antitrust; compliance; banks; competition